“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
https://www.jstor.org/stable/10.5406/jazzculture.2.2019.0059
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; care; discipline; discours dominant; femmes* artistes; genre; histoire; histoire et politique; identités LGBTQIA2+; maternité; montréal; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; éthique

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

« Une ‘mauvaise mère’ nommée Québec » dans Un Québec en mal d'enfants: la médicalisation de la maternité, 1910-1970 - Baillargeon, Denyse (Un Québec en mal d'enfants: la médicalisation de la maternité, 1910-1970, 2004)
Comment les médecins sont-ils parvenus à convaincre les femmes de la nécessité de les consulter, non seulement au moment de l’accouchement mais aussi durant la grossesse et, par la suite, durant la première année de leur enfant? Pourquoi et à quelles conditions celles-ci ont-elles choisi de suivre leurs prescriptions? Denyse Baillargeon répond à ces questions en s’attardant aux différents aspects du processus de médicalisation de la maternité entre les années 1910 et 1970. Son analyse s’intéresse au discours des médecins canadiens-français à l’égard de la mortalité infantile et de la maternité et au développement des services médicaux mis gratuitement à la disposition des mères durant cette période. Fondé sur une vaste recherche documentaire, et sur une soixantaine d’entrevues avec des femmes, cet ouvrage fait ressortir la multiplicité des acteurs sociaux qui ont pris part à ce processus et souligne les alliances, les conflits et les jeux de pouvoir qui les ont rassemblés ou opposés, pour révéler toute la complexité d’un phénomène qui a profondément transformé la maternité et la société québécoise.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droit des femmes*; famille; his4523; histoire; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques